Use and effectiveness of dapagliflozin in routine clinical practice: An Italian multicentre retrospective study. Issue 7 (30th March 2018) - Fadini, Gian Paolo; Zatti, Giancarlo; Baldi, Ileana; Bottigliengo, Daniele; Consoli, Agostino; Giaccari, Andrea; Sesti, Giorgio; Avogaro, Angelo; ,
Abstract : In randomized controlled trials (RCTs), sodium‐glucose co‐transporter‐2 (SGLT2) inhibitors have been shown to confer glycaemic and extra‐glycaemic benefits. The DARWIN‐T2D (DApagliflozin Real World evIdeNce in Type 2 Diabetes) study was a multicentre retrospective study designed to evaluate the baseline characteristics of patients receiving dapagliflozin vs those receiving selected comparators (dipeptidyl peptidase‐4 inhibitors, gliclazide, or glucagon‐like peptide‐1 receptor agonists), and drug effectiveness in routine clinical practice. From a population of 281 217, the analysis included 17 285 patients initiating dapagliflozin or comparator glucose‐lowering medications (GLMs), 6751 of whom had a follow‐up examination. At baseline, participants starting dapagliflozin were younger, had a longer disease duration, higher glycated haemoglobin (HbA1c) concentration, and a more complex history of previous GLM use, but the clinical profile of patients receiving dapagliflozin changed during the study period. Dapagliflozin reduced HbA1c by 0.7%, body weight by 2.7 kg, and systolic blood pressure by 3.0 mm Hg. Effects of comparator GLMs were also within the expected range, based on RCTs. This real‐world study shows an initial channelling of dapagliflozin to difficult‐to‐treat patients. Nonetheless, dapagliflozin provided significant benefits with regard to glucose control, body weight and blood pressure that were in line with findings from RCTs.